FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI DKI JAKARTA - Carissa Stella Wibowo; Eddy Joni (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study is to determine whether the factors of taxpayer awareness, tax sanctions, tax service quality, tax socialization, tax knowledge, compliance costs and moral obligations affect the compliance of motor vehicle taxpayers in DKI Jakarta. This study uses primary data with media questionnaires distributed by google form. The sample criteria used are motor vehicle taxpayers who are registered at the DKI Jakarta SAMSAT Office, have received the services by tax officer, and do their own tax payments. The sampling method used is convenience sampling and the number of samples obtained is 90 respondents. The data analysis method used is validity test, reliability test, classical assumption test, correlation coefficient analysis, coefficient determination analysis (adj R2), f test, and t test. The results of the analysis show that taxpayer awareness has an effect on motor vehicle taxpayers compliance. Meanwhile, tax sanctions, tax service quality, tax socialization, tax knowledge, complance costs and moral obligations have no effect on motor vehicel taxpayers compliance